Romanticism : A Very Short Introduction - Ferber, Michael (Oxford, New York Oxford University Press, 2010)
The only short introduction to Romanticism that incorporates not only the English but the Continental movements, and not only literature but music, art, religion, and philosophy.-publisher description.
Include Illustration, Appendix and Index
Keywords: Romanticism -- Europe